2015
DOI: 10.1371/journal.pone.0129328
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Availability Alters the Effects of Silver Nanoparticles on Periphyton Growth and Stoichiometry

Abstract: Exposure to silver nanoparticles (AgNPs) may alter the structure and function of freshwater ecosystems. However, there remains a paucity of studies investigating the effects of AgNP exposure on freshwater communities in the natural environment where interactions with the ambient environment may modify AgNP toxicity. We used nutrient diffusing substrates to determine the interactive effects of AgNP exposure and phosphorus (P) enrichment on natural assemblages of periphyton in three Canadian Shield lakes. The la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…We expected to observe significant effects of AuNP on wetland autotrophs, as AuNPs have been found to induce toxicity and to be bioavailable for different model organisms (Barrena et al 2009, Sabo-Attwood et al 2012, Tsyusko et al 2012, Glenn and Klaine 2013. We anticipated significant treatment interactions between nutrient enrichment and both NPs, as previous studies have reported interactive effects of nutrient enrichment and pollutants on algal and periphyton stoichiometry and on macrophyte growth (Fulton et al 2009, Das et al 2014, Norman et al 2015. However, the direction of this interaction was difficult to predict as nutrient availability may either compensate for or enhance the impact of metal pollution on aquatic primary producers (Gessner and Tlili 2016).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…We expected to observe significant effects of AuNP on wetland autotrophs, as AuNPs have been found to induce toxicity and to be bioavailable for different model organisms (Barrena et al 2009, Sabo-Attwood et al 2012, Tsyusko et al 2012, Glenn and Klaine 2013. We anticipated significant treatment interactions between nutrient enrichment and both NPs, as previous studies have reported interactive effects of nutrient enrichment and pollutants on algal and periphyton stoichiometry and on macrophyte growth (Fulton et al 2009, Das et al 2014, Norman et al 2015. However, the direction of this interaction was difficult to predict as nutrient availability may either compensate for or enhance the impact of metal pollution on aquatic primary producers (Gessner and Tlili 2016).…”
Section: Introductionmentioning
confidence: 98%
“…, Norman et al. ). The deleterious effects of synthetic chemicals may be amplified under high nutrient loads due to increased uptake rates and faster transfer of the contaminants through exposed food webs (Berglund ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have also emphasized the important role of aggregation for the production of toxic effects on algae by other types of NMs (Fleischer et al ; Madigan et al ; Navarro et al ; Oh and Park ). Furthermore, the low zeta potential for Cloisite 30B (–11 mV) could also result in important nutrients (e.g., phosphorus) binding to the nanoclay, which then limits the amount of nutrients available to algae (in part because the bound nutrient is now too large to pass through the pores of cell walls; Xiu et al ; Norman et al ). Differences in the ability of nanoclay type to form aggregates could also result in nanoclays having different toxic effects on benthic and pelagic organisms.…”
Section: Discussionmentioning
confidence: 99%